Work Group Climate and Behavioral Responses to Psychological Contract Breach - Shen, Yimo; Schaubroeck, John M.; Zhao, Lei; Wu, Lei (Frontiers in Psychology, 2019)
Drawing on theories of social exchange and social information processing, we examined whether the influence of psychological contract breach on in-role performance and organization-directed citizenship behavior (OCBO) depends work group climate levels, specifically procedural justice climate and power distance climate. The findings supported our hypothesis that psychological contract breach exhibits a stronger influence on in-role performance and OCBO among members of units with favorable procedural justice climates. Support for a hypothesized moderating role of power distance climate was less conclusive. We discuss the implications of our model and findings for theories of employee-organization relationships and practice.